2022
DOI: 10.1103/physrevb.105.075136
|View full text |Cite
|
Sign up to set email alerts
|

Spin texture in doped Mott insulators with spin-orbit coupling

Abstract: A hole injected into a Mott insulator will gain an internal structure as recently identified by exact numerics, which is characterized by a nontrivial quantum number whose nature is of central importance in understanding the Mott physics. In this work, we show that a spin texture associated with such an internal degree of freedom can explicitly manifest after the spin degeneracy is lifted by a weak Rashba spin-orbit coupling (SOC). It is described by an emergent angular momentum J z = ± 3 2 as shown by both ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…So far, present and existing spin-resolved ARPES results have found no signature of a band splitting other than the bilayer splitting. It is thus apparent that further theoretical work is needed to go beyond the conventional framework of Rashba-type spin–orbit interactions 6 8 , which cannot explain the current results where no Rashba-like band-splitting is observed.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…So far, present and existing spin-resolved ARPES results have found no signature of a band splitting other than the bilayer splitting. It is thus apparent that further theoretical work is needed to go beyond the conventional framework of Rashba-type spin–orbit interactions 6 8 , which cannot explain the current results where no Rashba-like band-splitting is observed.…”
Section: Discussionmentioning
confidence: 70%
“…Conversely, recent spin- and angle-resolved photoemission spectroscopy (ARPES) measurements on high- cuprates have shown significant spin polarization, implying the presence of spin–momentum locking induced by the spin–orbit interaction 5 . This has prompted theoretical investigations into the role and consequences of the Rashba-type spin–orbit interaction in cuprate superconductors, highlighting the potential importance of this interaction in high- cuprates 6 8 . However, the driving force behind the reported spin-polarized electronic states remains unclear, perhaps due to their unique spin texture, which involves a sign reversal of spin polarization from the node to off-nodes, even within one Fermi surface.…”
Section: Introductionmentioning
confidence: 99%
“…( 20) with finite-size ED and DMRG results outlined in Subsection 2.3, as calculated by the VMC method, including the nontrivial angular momentum L z = ±1 in 2D [49] and the momentum structure in the two-leg ladder case, [48] clearly demonstrates that the doped hole in the Mottness gets substantially renormalized by the phase-string effect, whose behavior is fundamentally distinct from the celebrated Landau's quasiparticle as a new quasiparticle of the doped Mott insulator. Recently a single-hole-doped case under a perturbation of a weak spin-orbit coupling (SOC) has been also examined, [50] which 087104-6 has further shown that the twisted hole with the novel angular momentum in Eq. ( 21) is critical to properly describe the response to the SOC as indicated by an excellent agreement between the VMC and ED.…”
Section: One-hole and Two-hole Ground Statesmentioning
confidence: 99%